Method for improving gelation activity of waste glass powder through physical and chemical synergistic activation
Through the physical and chemical synergistic activation method, the use of segmented feeding and optimizing the ball milling process has significantly improved the gelling activity of waste glass powder, solved the problems of low activation efficiency and unstable effect, and achieved efficient and stable activation effect.
Patent Information
- Application Number
- CN202411647183.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The application of waste glass powder in building materials is restricted by the problems of insufficient gelling activity, low activation efficiency, unstable activation effect and poor controllability of the activation process.
The physical and chemical synergistic activation method is adopted, and waste glass and chemical activator are put into the ball mill through a segmented feeding strategy, combining optimized ball mill process parameters and four-stage grinding balls to achieve physical and chemical synergistic activation.
It significantly improves the gelling activity of waste glass powder, improves the activation efficiency and stability of the effect, ensures the controllability of the activation process, and meets the needs of building materials application.
Smart Images

Figure BDA0005139963190000051 
Figure BDA0005139963190000061 
Figure BDA0005139963190000062
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building cement preparation, and in particular relates to a physical and chemical synergistic activation method for improving the cementing activity of waste glass powder. Background Art
[0002] With the acceleration of urbanization, the amount of waste glass generated has increased year by year. The treatment and resource utilization of waste glass has become an environmental problem that needs to be solved urgently. Since waste glass is mainly composed of silicon dioxide, calcium oxide and other components, its chemical composition is similar to auxiliary cementitious materials such as fly ash, so it is of great application value to use waste glass powder as an auxiliary cementitious material in building materials.
[0003] However, the current application of waste glass powder in building materials still faces the following technical difficulties: (1) The gelling activity of waste glass powder is insufficient. The waste glass powder obtained by conventional mechanical grinding has low activity and is difficult to meet the needs of actual engineering applications, which limits its application ratio in building materials (Zhao Haidong et al., 2018); (2) The existing activation methods are inefficient. Traditional physical activation methods have high energy consumption and low efficiency, while single chemical activation methods have unstable effects and high costs (Ke Guojun et al., 2015); (3) The activation process has poor controllability. The existing activation process parameters are not optimized enough, making it difficult to achieve a controllable improvement in the activity of waste glass powder, resulting in large fluctuations in product quality (Mejdi et al., 2019).
[0004] Therefore, it is urgent to develop an efficient, stable and controllable method for activating waste glass powder to enhance its gelling activity, promote the resource utilization of waste glass, and achieve the unity of environmental and economic benefits. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the gelling activity of waste glass powder through physical and chemical synergistic activation, aiming to solve the current technical problems of insufficient gelling activity of waste glass powder, low activation efficiency and unstable activation effect of traditional activation technology.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions.
[0007] The invention provides a method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation. The method adopts a staged feeding strategy to feed waste glass and a chemical activator into a ball mill, and performs synergistic activation treatment through optimized ball milling process parameters.
[0008] Further optimized waste glass raw material requirements:
[0009] 1) Raw material type: Soda-lime waste glass, including building glass, beverage bottle glass or daily glass products
[0010] 2) Chemical composition requirements: SiO2 content ≥ 65%, CaO content 15-25%, Na2O content 10-15%
[0011] 3) Particle size requirement before activation: D90≤80μm
[0012] 4) Specific surface area before activation: 350~400m 2 / kg
[0013] 5) Moisture content: ≤1%.
[0014] Further optimized, the chemical activator is selected from any one of silica fume, nano-silicon dioxide, nano-titanium dioxide, calcite, and alum, and the activity of the waste glass powder is synergistically improved through the chemical activation effect of the activator and the physical activation effect of mechanical ball milling.
[0015] Further optimized, the chemical activator performance requirements are:
[0016] 1) Silica fume: specific surface area ≥15000m 2 / kg, SiO2 content ≥ 90%
[0017] 2) Nano-silicon dioxide: specific surface area ≥180000m 2 / kg, purity ≥99%
[0018] 3) Nano titanium dioxide: specific surface area ≥150000m 2 / kg, purity ≥98%
[0019] 4) Calcite: Specific surface area ≥ 800m 2 / kg, CaCO3 content ≥ 95%
[0020] 5) Alum: KAl(SO4)2, analytical grade,
[0021] Further optimized, the segmented feeding strategy includes two stages:
[0022] 1) The first stage: 70% waste glass and 80% activator are input;
[0023] 2) The second stage: 30% waste glass and 20% activator are added. The material agglomeration can be effectively avoided by adding materials in stages, thus improving the ball milling efficiency.
[0024] Further optimized, the ball milling process adopts a variable speed intermittent process of "high-speed ball milling-staying-medium-speed ball milling":
[0025] 1) High speed section: ball mill speed is 55-60r / min (80-85% of critical speed) for 20 minutes;
[0026] 2) Dwelling period: 5 minutes;
[0027] 3) Medium speed section: run at 55-65% of the critical speed for 15 minutes;
[0028] 4) After each section of feeding, cycle 3 times.
[0029] Further optimized, the ball milling medium uses four-graded grinding balls:
[0030] 1) 20%
[0031] 2) 30%
[0032] 3) 30%
[0033] 4) 20%.
[0034] Further optimized, the performance index requirements of the activated product are:
[0035] 1) Physical properties:
[0036] Specific surface area: 500~600m 2 / kg; particle size distribution: D90≤45μm, D50≤15μm
[0037] 2) Activity index: 7d activity index ≥ 75%; 28d activity index ≥ 90%
[0038] 3) Working performance: initial setting time: ≥45min; final setting time: ≤600min.
[0039] Further optimized, the activation process control requirements:
[0040] 1) Ball mill material-ball ratio: 4:1~5:1
[0041] 2) Ball milling temperature: ≤60℃
[0042] 3) Equipment speed fluctuation: ±2r / min
[0043] 4) Time interval between segmented feeding: 10 to 15 minutes.
[0044] Compared with the prior art, the present invention has the following advantages and technical effects:
[0045] The present invention solves the problems of insufficient gelling activity of waste glass powder, low activation efficiency, unstable activation effect, etc. The method adopts a staged feeding strategy to put waste glass and chemical activator (any one of silica fume, nano silicon dioxide, nano titanium dioxide, calcite, and alum) into a ball mill, and adopts a variable speed intermittent process of four-graded grinding balls and "high-speed ball milling-staying-medium-speed ball milling" to significantly improve the gelling activity of waste glass powder through physical and chemical synergistic activation. The method has the characteristics of high activation efficiency, significant activity improvement, and controllable process, and can be widely used in the resource utilization of waste glass powder. DETAILED DESCRIPTION
[0046] The implementation of the present invention is further described below in conjunction with specific embodiments, but the implementation and protection of the present invention are not limited thereto.
[0047] Example 1
[0048] 1. Raw material preparation:
[0049] 1) Waste glass: Use waste glass from buildings, the main chemical composition is SiO268.5%, CaO 18.2%, Na2O12.3%, the specific surface area before activation is 372m 2 / kg, D 90 The particle size is 75 μm and the moisture content is 0.8%.
[0050] 2) Activator: Silica fume with a specific surface area of 16500m 2 / kg, SiO2 content 87.3%.
[0051] 2. Activation process:
[0052] 1) Staged feeding: In the first stage, 70% waste glass (3.5kg) and 80% silica fume (0.04kg) are fed; in the second stage, 30% waste glass (1.5kg) and 20% silica fume (0.01kg) are fed;
[0053] 2) Ball milling parameters: high speed section: 58r / min, lasting 20 minutes, residence period: 5 minutes, medium speed section: 42r / min, lasting 15 minutes, and 3 cycles after each section is filled;
[0054] 3. Ball milling media: four-level grinding balls ( 20% 30% 30% 20%), material-to-ball ratio: 4.5:1.
[0055] Example 2
[0056] 1. Raw material preparation:
[0057] 1) Waste glass: Waste glass from beverage bottles, the main chemical composition is SiO271.2%, CaO 16.8%, Na2O11.5%, the specific surface area before activation is 385m 2 / kg, D90 is 72μm, and the moisture content is 0.6%.
[0058] 2) Activator: Nano-silicon dioxide with a specific surface area of 185,000 m 2 / kg, purity 99.2%.
[0059] 2. Activation process:
[0060] 1) Staged feeding: 70% waste glass (3.5kg) and 80% nano-silicon dioxide (0.04kg) are fed into the first stage; 30% waste glass (1.5kg) and 20% nano-silicon dioxide (0.01kg) are fed into the second stage;
[0061] 2) Ball milling parameters: high speed section: 57r / min, lasting 20 minutes, residence period: 5 minutes, medium speed section: 40r / min, lasting 15 minutes, and 3 cycles after each section is filled;
[0062] 3. Ball milling media: four-level grinding balls ( 20% 30% 30% 20%); material-to-ball ratio: 4.8:1.
[0063] Example 3
[0064] 1. Raw material preparation:
[0065] 1) Waste glass: Daily glass products are used, the main chemical composition is SiO269.8%, CaO 17.5%, Na2O11.8%, the specific surface area before activation is 368m 2 / kg, D90 is 78μm, and the moisture content is 0.9%.
[0066] 2) Activator: Alum, analytical grade.
[0067] 2. Activation process:
[0068] 1) Staged feeding: In the first stage, 70% waste glass (3.5 kg) and 80% alum (0.04 kg) are fed; in the second stage, 30% waste glass (1.5 kg) and 20% alum (0.01 kg) are fed;
[0069] 2) Ball milling parameters: high speed section: 56r / min, lasting 20 minutes, residence period: 5 minutes, medium speed section: 39r / min, lasting 15 minutes, and 3 cycles after each section is filled;
[0070] 3) Ball milling media: four-level grinding balls ( 20% 30% 30% 20%), material-to-ball ratio: 4.2:1.
[0071] Comparative Example 1 (single physical activation):
[0072] The same waste glass raw material as in Example 1 is used, no chemical activator is added, and only ball milling is performed;
[0073] Comparative Example 2 (single chemical activation):
[0074] The same waste glass raw materials and silica fume as in Example 1 were used and simply mixed;
[0075] Comparative Example 3 (high ball to material ratio):
[0076] The material-to-ball ratio is increased to 6:1 (exceeding the 4:1-5:1 in the claim), and other conditions are the same, and silica fume is used as an activator.
[0077] Comparative Example 4 (improper proportion of segmented feeding):
[0078] 1) The first stage: 55% waste glass and 90% activator are input;
[0079] 2) The second stage: 45% waste glass and 10% activator are added, and other conditions are the same, and silica fume is used as the activator.
[0080] Comparative Example 5 (inappropriate activator):
[0081] 1) Ordinary silica powder (specific surface area 8000m 2 / kg, lower than the requirement of ≥15000m 2 / kg; SiO2 content 85%, lower than the requirement ≥90%), other conditions are the same.
[0082] Comparative Example 6 (Insufficient number of cycles):
[0083] 1) Each stage of feeding is cycled only once (less than the required 2-4 times), other conditions are the same, and silica fume is used as the activator
[0084] Performance test results:
[0085] Table 1 Particle characteristics
[0086]
[0087] Table 2 Basic performance
[0088]
[0089] Table 3 Activity index
[0090]
[0091] Test method description:
[0092] Activity index: measured according to "GB / T 18736-2017 Mineral admixtures for high-strength and high-performance concrete", activity index = (compressive strength of admixture group / compressive strength of reference group) × 100%;
[0093] Water consumption for standard consistency, setting time and final setting time: Determined in accordance with "GB / T 1346-2011 Test method for water consumption, setting time and stability of cement for standard consistency".
[0094] From Tables 1 to 3, we can see that:
[0095] 1. The physical and chemical synergistic activation has a significant effect on the fineness of waste glass powder.
[0096] 2. The standard consistency water consumption of waste glass powder after physical and chemical synergistic activation is 28.5-29.2%, which is slightly higher than the control ratio, but the change is small, indicating that the activation process has little effect on water consumption. The setting time is moderate, the initial setting time is between 180-195 minutes, and the final setting time is between 478-495 minutes, which meets the requirements of engineering applications.
[0097] 3. All three activators can significantly improve the activity of waste glass powder, with the activity index reaching 77.5-81.2% at 7d and 91.8-94.5% at 28d. The order of activity index improvement is: nano-silica > alum > silica fume. Compared with single physical activation (7d: 65.3%, 28d: 82.1%) and single chemical activation (7d: 58.5%, 28d: 75.6%), the synergistic activation effect is significantly improved.
[0098] 4. Although some comparative examples adopt the idea of physical and chemical synergistic activation, the activation effect is not as good as that of the embodiments because the key process parameters exceed the limited range of the present invention. Among them, the comparative example 3 has a high material-ball ratio (6:1), which exceeds the optimal range of 4:1 to 5:1 of the present invention, resulting in reduced ball milling efficiency and limited activity improvement. Although the activity index is better than single physical activation and chemical activation, its 28d activity index is only 85.6%, which is much lower than 92.3% in Example 1.
[0099] 5. Comparative Example 4 uses an unreasonable staged feeding ratio. The activator ratio in the first stage is too high (90%), which is easy to cause agglomeration, and the waste glass ratio in the second stage is too high (45%), which is not conducive to uniform activation. This deviation in feeding ratio affects the dispersion of materials and activation uniformity. Its 28d activity index is 84.8%, indicating that a reasonable staged feeding ratio plays an important role in improving the activation effect.
[0100] 6. Comparative Example 5 uses ordinary silicon powder as an activator, and its specific surface area (8000m 2 / kg) and purity (85%) do not meet the requirements of the present invention. The lower specific surface area leads to a reduced contact area with waste glass, and the lower purity affects the reactivity of the activator, and the final 28d activity index is only 83.2%. This shows that the performance index of the activator has a significant impact on the synergistic activation effect.
[0101] 7. In Comparative Example 6, the number of cycles is insufficient (only 1 time), which is lower than the requirement of 2 to 4 times in the present invention, resulting in insufficient physical activation of waste glass powder, insufficient contact time between the activator and waste glass, and limited chemical activation effect. Its 28d activity index is 83.8%, which fully illustrates the importance of sufficient number of cycles to ensure activation effect.
[0102] In summary, physical activation increases the specific surface area and surface activity through mechanical force, and the chemical activator reacts chemically with the glass surface during ball milling to form new active products. The two activation methods promote each other and produce a synergistic effect. In addition, considering the activation effect and economic efficiency, it is recommended to use nano-silicon dioxide as the activator, adopt staged feeding and variable speed intermittent ball milling process, strictly control the process parameters, and ensure stable product quality.
[0103] The physical and chemical synergistic activation method proposed in the present invention significantly improves the gelling activity of waste glass powder by optimizing process parameters and selecting appropriate activators, and provides a feasible technical solution for the resource utilization of waste glass.
Claims
1. A method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation, characterized in that: The following steps are involved: The waste glass and chemical activator are put into the ball mill by adopting the staged feeding strategy, and the synergistic activation treatment is carried out by controlling the ball milling process parameters to improve the gelling activity of the waste glass powder. The ball milling process comprises: 1) High speed section: 80-85% of the critical speed, lasting 15-25 minutes; 2) Dwelling period: 3 to 7 minutes; 3) Medium speed section: 55-65% of the critical speed, lasting 10-20 minutes; 4) After each section is filled, it is circulated 2 to 4 times; The ball milling process parameters include: 1) The ball mill material-ball ratio is 4:1-5:1; 2) Ball milling temperature ≤ 60°C; 3) Equipment speed fluctuation is controlled within ±2r / min; 4) The time interval between each feeding is 10 to 15 minutes.
2. The method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation according to claim 1, characterized in that: The waste glass is soda-lime waste glass, including one or more of building glass, beverage bottle glass or daily glass products.
3. The method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation according to claim 2, characterized in that: The waste glass raw material meets the following requirements: 1) Main chemical composition requirements: SiO2 content ≥ 65%, CaO content 15-25%, Na2O content 10-15%; 2) Particle size before activation D 90 ≤80μm; 3) The specific surface area before activation is 350-400m 2 / kg; 4) Moisture content ≤1%.
4. The method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation according to claim 1, characterized in that: The chemical activator is selected from one or more of silica fume, nano silicon dioxide, nano titanium dioxide, calcite and alum.
5. The method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation according to claim 1, characterized in that: The segmented feeding strategy includes: 1) The first stage: 65-75% waste glass and 75-85% chemical activator are input; 2) The second stage: input 25-35% waste glass and 15-25% chemical activator.
6. The method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation according to claim 1, characterized in that: The ball milling medium adopts four-grade grinding balls: 1) Diameter Accounting for: 18-22%; 2) Diameter Accounting for: 28-32%; 3) Diameter Accounting for: 28-32%; 4) Diameter Accounting for: 18~22%.
7. The method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation according to claim 1, characterized in that: The specific surface area of the waste glass before activation is 350 to 400 m 2 / kg, the specific surface area after activation is 500~600m 2 / kg.
8. The method for improving the gelling activity of waste glass powder by physical and chemical synergistic activation according to claim 1, characterized in that: The performance requirements of the chemical activator are: 1) Silica fume: specific surface area ≥15000m 2 / kg, SiO2 content ≥90%; 2) Nano-silicon dioxide: specific surface area ≥180000m 2 / kg, purity ≥99%; 3) Nano titanium dioxide: specific surface area ≥150000m 2 / kg, purity ≥98%; 4) Calcite: Specific surface area ≥ 800m 2 / kg, CaCO3 content ≥95%; 5) Alum: analytically pure, KAl(SO4)2 content ≥98%.
9. The waste glass powder according to claim 1 obtained by the method according to any one of claims 1 to 8.
10. The waste glass powder according to claim 9, characterized in that: It has the following characteristics: 1) Particle size distribution meets: D 90 ≤55μm, D 50 ≤15μm; 2) Specific surface area is 500~600m 2 / kg; 3) Initial setting time ≥45min, final setting time ≤600min; 4) 7-day activity index ≥ 75%, 28-day activity index ≥ 90%.
Citation Information
Patent Citations
Composition of materials for production of acid resistant cement and concrete and methods thereof
CA2416705A1
Glass powder products for use as a pozzolan, and processes and systems for the production thereof
CA3156214A1
Performance adjustment material for activating steel slag at high temperature and application thereof
CN101560578A
Heavy-duty anticorrosive coating for flue gas desulphurization equipment and preparation technology thereof
CN102690586A
Preparation method of cement mortar
CN103922653A